G471 The renal status of the uk juvenile – sle cohort. (27th April 2015) - Oni, L; Richards, E; Smith, E; Beresford, MW
Abstract : Systemic lupus erythematosus (SLE) is a life-long severe disease; juvenile-onset (JSLE) patients experience more lupus nephritis (LN) and progression to chronic kidney disease (CKD) occurs in some patients. Earlier detection of CKD in other conditions provides an opportunity to delay the rate of renal deterioration. Using a cross sectional analysis of participants recruited to the UK JSLE Cohort Study, the aim of this study was to assess the current renal function status and the presence of CKD associated factors (hypertension, proteinuria, hypercholesterolaemia, anaemia) in a cohort of JSLE patients. The study cohort (n = 250) was aged 12.6 (10.2–14.3) years at diagnosis and 217 (87%) were female. The latest American College Rheumatology SLE score was 5 (4–7). The patients had JSLE for 3.8 (2.1–6.2) years, and a global British Isles Lupus assessment group index score of 2 (1–4). Seventy-nine (32%) patients had abnormal renal function; 43 (17%) had hyperfiltration (eGFR >140 ml/min/1.73m 2 ), 24 (10%) had an eGFR 60–89 ml/min/1.73m 2, 8 (3%) had an eGFR 30–59 ml/min/1.73m 2, no patients had an eGFR 15–29 ml/min/1.73m 2 and 4 (2%) had an eGFR <15 ml/min/1.73m 2 . Hyperfiltration was associated with the presence of proteinuria (>500mg/day), seen in 32% (p = 0.03). With regards to CKD associated factors, hypertension was common in all renal function groups (26% of patients) and associated with reduced eGFR (p = 0.03) and proteinuria (p = 0.01). Hypercholesterolaemia only occurred in 10 patients (7%). Proteinuria correlated with the presence of hypertension (p = 0.014). Anaemia was not associated with renal function but with global disease activity. This large UK wide inception cohort has demonstrated the burden of renal disease in JSLE. Recent studies have suggested renal hyperfiltration may have clinical significance, as it is independently associated with later renal function decline and cardiovascular disease in other conditions. This study may have identified JSLE patients at high-risk of CKD progression and it highlights three key findings; children with JSLE may have impaired renal function, CKD associated factors are common and shared care between Paediatric Rheumatology and Nephrology is required. Further confirmatory studies are required as early identification, combined with aggressive blood pressure management and reduction of proteinuria, may slow the rate of renal function decline in this population.